evaluating mathematical expressions
![Evaluating Mathematical Expressions class=](https://ph-static.z-dn.net/files/db4/767b2153ec08d4916d2432afede96f9b.jpg)
Answer:
A.
1) 2(6) + 3(4)
12 + 12 = 24
2) 6 + 2(4) - (-2)
6 + 8 + 2 = 16
3) 3(6) - 2(4) + 5
18 - 8 + 5= 15
4) 2 [ 6- 3(4) ]
2 (-6) = -12
5) 6 - 2(4) + 3(-2)
6 - 8 - 6 = -8
6) 2 [ 2(6) + 4(4) - (-2) ]
2 (30) = 60
7) -2 [ 2(6) + 4 ]
- 2 (16) = - 32
8) - [ 6 + 2(4) - 3(-2) ]
- (20) = - 20
9) - 2(6) + 4(6) (-2)
- 12 - 48 = - 60
10) 5 (6) (4) (-2) - 3 (-2 - 4)
- 240 + 18 = - 222
B.
1) 0.2 - [ 2(1) + 3(0.2) ] - 2(1)
0.2 - 2.6 - 2 = - 4.4
2) 3(0.2) - [ 2(1) - 5(0.2) ] - 9(1)
0.6 - 1 - 9 = -9.4
3) [ 2(-2)-3(1) ] - [ 8(-2) - 6 + 4(3) ]
7 + 15 = 22
4) 12 (1/2) + (-2) (6) (3)
6 - 36 = - 30
5) 2(-2) (0.2) + 3(6) (1/2) - 5(3) (0.2)
- 0.8 + 9 - 3 = 5.2
6) 4 [ (1/2) + (-3/4) ]
4 (-1/4) = - 1
7) [ (100(0.2) ]^2
(20)^2 = 400
8) -2 [ ( 8-3 ( -3/4 ) ] + 4(-2) (1/2)
-2 (10.25) - 4 = -24.5
9) 7(-2) (6) + (6) (3) / (1/2)
- 66 / (1/2) = - 132
10) - 2^2 + 6^2 / 2 + 3^2
32 / 11 = 2.909 OR 2.91